RETROPERITONEOSCOPIC HEMINEPHRECTOMY: INITIAL EXPERIENCE IN CIPTO MANGUNKUSUMO HOSPITAL JAKARTA - Irdam, Gampo Alam; Wahyudi, Irfan; Rodjani, Arry; Situmorang, Gerhard Reinaldi (Indonesian Journal of Urology, 2015)
Objective: To explain efficacy and feasibility of heminephrectomy laparoscopic with retroperitoneal approach in double collecting system patients with non-functional upper moiety. Material & methods: Three cases in Cipto Mangunkusumo Hospital’s urology outpatient clinic from July 2013 - January 2014 with double collecting system and non-functional upper moiety. Laparoscopic heminephrectomy with retroperitoneal approach were done to these patients. Results: Surgery was done within 200 - 240 minutes with minimal bleeding and no significant complication. There was no significant hemodynamic disturbance observed during surgery. Patients were able to mobilize and to get immediate oral intake. Pains were minimal and can be treated with first-line analgesics. The patients were discharged on the fourth and fifth day of hospitalization. Conclusion: We are reporting our initial experience doing retroperitoneoscopic heminephrectomy in double collecting system patient. This procedure was feasible and produced good outcomes for the patients.